Strategi Kepala Sekolah Mengembangkan Budaya Islami Di SMP Islam Terpadu Se Kecamatan Tanayan Raya Pekanbaru - Tika Emilda (LPPM STAI Diniyah Pekanbaru, 2020)
This journal aims to find out the strategies that can be carried out by school principals to develop Islamic culture for schools characterized by Islam (Integrated Islam). The results of research conducted in all SMPs in Tanayan Raya Pekanbaru District, almost all school principals have implemented Islamic culture that is the hallmark of Integrated Islamic Schools (IT) including principals implementing policies to familiarize themselves with S3 (greetings, smiles, and greetings), getting used to shaking hands between teacher and teacher and with students, getting used to praying before and after learning, reading the Qur'an, getting used to praying the Dhuha Zhuhur and Asr in the congregation, Muhadarah. In addition to the above policy, the principle also applies the Exemplary method, familiarizes good things, enforces discipline, provides motivation, and cooperation with parents in upholding Islamic culture